Electrospun cellulose filters with antiviral properties: review of developments in the last 5 years - Hadzhieva, Zoya; Bider, Faina; Kissel, Hannah; Damian-Buda, Andrada-Ioana; Boccaccini, Aldo R. (Chemical Engineering Journal Advances, 2025)
Ongoing global health and environmental crises, such as the outbreak of infectious diseases, contaminated drinking water sources, or air pollution, have increased the demand for exploring functional nonwovens for filtering applications. The current paper presents a literature review on filters made of biodegradable cellulose via electrospinning with antiviral capabilities. Initially, a short overview of the filtration process in relation to the aim application (air or water filtration) is provided. Furthermore, the electrospinning technique, including its setup, parameter adjustments, and potential geometric fiber outcomes is presented considering the targeted applications. The suitability of natural biodegradable cellulose (and its derivatives) for producing nonwoven electrospun antiviral filters is discussed. Finally, a comprehensive summary of the recent publications (2020–2024) reporting on electrospun cellulose-based filters with antiviral properties is provided, followed by a brief discussion on the current challenges and future perspectives in this field.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Antiviral; Cellulose; Electrospinning; Filter; Review